Nurses’ professional quality of life and job satisfaction in Jordan - Hamdan, Khaldoun M.; Allari, Rabia S.; Baghdadi, Nadiah A.; Andargeery, Shaherah Yousef; Haymour, Abdullah M.; Sabrah, Evan; Shaheen, Abeer M. (Frontiers in Medicine, 2024)
BackgroundProfessional quality of life has received widespread concern in nursing over the last few years. Nurses with a high professional quality of life enthusiastically approach their work and provide excellent patient care. On the other hand, poor professional quality of life may affect nurses’ quality of care, resulting in job dissatisfaction and jeopardizing patient outcomes.AimTo examine the relationship between the professional quality of life and job satisfaction among registered nurses.MethodA cross-sectional correlational design and convenience sampling were used. Data were collected using the Professional Quality of Life Scale-Health and the Job Satisfaction Survey.ResultsThe mean total score for the nurses’ job satisfaction survey was high 117.47 (SD = 27.26). The nature of work subscale had the highest mean, while the fringe benefits subscale had the lowest. The mean total score for the Professional Quality of Life Scale for Health Workers was moderate 98.41 (SD = 12.15). The Compassion Satisfaction subscale had the highest mean score, while the moral distress subscale had the lowest. There was a statistically significant positive relationship between nurses’ job satisfaction and professional quality of life for health workers.ConclusionNursing supervisors need to be more aware of the variables influencing nurses’ professional quality of life and job to assess the degree of moral distress and satisfaction. Although nurses offer their patients physical, psychological, and spiritual care, their duties and interactions with patients can have a negative impact on them. As a result, nurses will be better equipped to care for patients if they have the assistance and support they need.